Negotiating Religious Identity in Health Practices: Muslim Community Resistance to the Hegemonization of Secular Dietary Patterns in Indonesia - Riyanto, Ridho; Sulong, Sofan (Potret Pemikiran, 2025)
Indonesia faces a paradox as the world's most populous Muslim nation with a Muslim-majority population, yet diabetes prevalence reaches 11.1% among adults, with more than 40% of cases undiagnosed. Islamic health epistemology remains marginalized within the secular healthcare system inherited from Dutch colonialism. The dietary transition from traditional plant-based patterns to Western consumption, which began in the 1970s, correlates with an increase in adult obesity, reaching 35.4% in 2018. This study examines the negotiation of religious identity among Indonesian Muslim communities through dietary practices as a response to Western food hegemony and secular health governance in the context of diabetes prevention. This qualitative library research employs Critical Discourse Analysis on three categories of texts: religious (Qur'an, Hadith, tafsir), health policy (Balanced Nutrition Guidelines, regulations, medical curricula), and academic literature from 2010 to 2025. Analysis was conducted through data, methodological, and theoretical triangulation using frameworks of biopower, cultural hegemony, and epistemic injustice. Islamic dietary principles—halal, tayyib, al-i'tidal, and sawm—function as counter-hegemonic practices against neoliberal dietary colonialism. Structural barriers include biomedical hegemony that excludes Islamic epistemology; policy gaps with medical curricula adopting dominant Western content; and economic inequality limiting working-class access to quality halal-tayyib food. Ramadan fasting demonstrates metabolic benefits aligned with contemporary intermittent fasting research; however, it was previously discredited until validated by Western science. A pluralistic health framework is needed that integrates Islamic epistemology through curricular reform, policy co-design with religious authorities, and mosque-based diabetes prevention programs that recognize religious practices as legitimate health resources.